1982
DOI: 10.3109/00365528209182233
|View full text |Cite
|
Sign up to set email alerts
|

Brush Border and Lysosomal Marker Enzyme Profiles in Duodenal Mucosa from Coeliac Patients before and after Organ Culture

Abstract: Five brush border and 2 lysosomal enzymes were measured in duodenal tissue explants from 21 children and young adults (16 coeliac and 5 non-coeliac) before and after organ culture. Reduced activity of brush border enzymes and increased activity of lysosomal enzymes were recorded in flat mucosas from coeliac patients compared with remission coeliac explants and biopsy specimens from non-coeliac controls. Slightly increased activity of alkaline phosphate and sucrase was recorded during culture (24 h) of coeliac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Such means of assessment of cultured tissue enabled the organ culture technique to be used to provide an in vitro model of coeliac disease (Howdle et aL,198 lb). Other workers confirmed these results using similar morphometric measurements (Fluge and Aksnes, 1981;Bramble, Watson and Record, 1981;Olives et al, 1981).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Such means of assessment of cultured tissue enabled the organ culture technique to be used to provide an in vitro model of coeliac disease (Howdle et aL,198 lb). Other workers confirmed these results using similar morphometric measurements (Fluge and Aksnes, 1981;Bramble, Watson and Record, 1981;Olives et al, 1981).…”
supporting
confidence: 54%
“…The technique of organ culture for gastrointestinal mucosa Browning and Trier (1969) described a method which has been used, with minor modifications, by several groups of workers, including the present author (Falchuk et a!., 1974a;Jos et al, 1975;Fluge and Aksnes, 1981;Howdle et al, 1981a). Usually mucosal biopsies are obtained for culture using an intestinal mucosa biopsy instrument.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bread wheat 0 a-Gliadin [69] 0 A-gliadin [73] 0 Tryptic a-gliadin digest [74] 0 Peptic-tryptic gluten digest [66,69,71,72] 0 Peptic-tryptic gliadin digest [33, 75 -78] 0 Peptic-tryptic-cotazym gliadin digest [33, 74, 78 -80] 0 Peptic-tryptic a-gliadin digest [33,41,66,75,76] 0 Peptic-tryptic b-gliadin digest [33,41,75,76] 0 Peptic-tryptic c-gliadin digest [33,41,75,76] 0 Peptic-tryptic x-gliadin digest [33,41,75,76] 0 Peptide 2R derived from a peptic-tryptic-cotazym digest of gliadin [81] 0 Peptides fractionated from a peptic-tryptic-cotazym digest including peptide fractions B 2 and B 3142 [40,41]. Peptide B 3142 is homologous to A-gliadin amino acid sequence 3 -55 [42] …”
Section: Toxic Cereal Fractionsmentioning
confidence: 99%
“…These results were consistent with those by Hekkens et al (32) who demonstrated that an a-gliadin fraction, coded A-gliadin (10,49), was capable of producing changes in epithelial tissue characteristic of celiac disease when instilled directly into the small intestine of celiac patients and with those by Falchuk et al (19) showing that this fraction had adverse effects on biopsied intestinal epithelium. Huge and co-workers (24)(25)(26) have developed a morphological, morphometric, and biochemical assessment of human duodenal biopsies from celiac patients maintained in organ culture and have tested with this in vitro system several gliadin fractions including a-gliadin and Frazer's fraction I11 and subfractions. Biopsies from patients with untreated celiac disease were susceptible to gliadin fractions, which provoked disorganization of crypt architecture, reduced height, and irregularities of enterocytes and crypt cells, together with detrition of surface epithelial cells and even tissue necrosis.…”
mentioning
confidence: 99%